(untitled) (Voice: A Biannual & Bilingual Journal, 2025)
Shobha De’s fictions provide a thoughtful perspective on the complexities of urban life in India, especially the social dynamics of Mumbai. This research paper analyzes De’s portrayal of urban experiences in De’s novels Socialite Evenings (1989), Starry Nights (1991), Sisters (1992), and Snapshots (1995), focusing on themes such as consumerism, gender roles, personal freedom, social mobility, class division, and identity crisis. The paper examines the representation of the ambitions, worries, and dreams of the upper-middle and influential classes in the swiftly evolving cultural surroundings of post-liberalisation India.The study focuses on key thematic dimensions, including consumerism, gender roles, individual freedom, social class division, and identity crises. It explores how De’s characters find ways to the attractive yet competitive terrain of Mumbai, a city portrayed as both enabling and unforgiving. Using a qualitative research design, the study offers close textual analysis to examine the influence of metropolitan environments on characters’ psychology, relationships, and ambitions. Secondary scholarly sources are integrated to contextualize De’s narratives within the broader discourse of postmodern India, where rapid economic growth has reshaped social behaviour and cultural expectations. De presents Mumbai as a charismatic yet ruthless urban sight, where ambition grows bigger amid moral ambiguity. Her female characters deal with traditional patriarchal structures with strength, independence, and a lot of emotional depth. The study concludes that Shobha De’s novels offer a significant literary representation of late twentieth-century Indian urbanity. Her fictions disclose dynamic social, cultural, and psychological patterns that persist in shaping metropolitan life in modern India.